The Effects of Diverse Exercise on Cognition and Mental Health of Children Aged 5–6 Years: A Controlled Trial - Jia, Ningxin; Zhang, Xijin; Wang, Xu; Dong, Xiaosheng; Zhou, Yanan; Ding, Meng (Frontiers in Psychology, 2021)
The rate of learning and cognitive development is at its highest level in preschool-aged children, making this stage a critical period. Exercise has received increasing attention for its beneficial physical and mental health effects on the development of preschool children. This study investigated the effects of diverse exercise on the cognition of preschool children. Two classes were randomly selected from kindergarten classes of children aged 5-6 years, and designated as the experimental and control classes. Each class contained 20 children (10 boys and 10 girls) according to the kindergarten class system. The experimental class completed exercises according to the designed curriculum, while control class carried out exercises according to the regular teaching plan, for a study period of 12 weeks. The Wechsler Preschool and Primary Scale of Intelligence and the Mental Health Questionnaire for Children were used to assess outcomes, both at the beginning and end of study. After 12 weeks, the experimental class has improved in the "Object Assembly", "Block Design", "Picture Completion" and " Coding" (14.70±2.14, p<0.01; 14.54±1.56, p<0.01; 9.62±2.06, p<0.05; 15.92±2.72, p<0.05) in performance test, and showed improvements in the "Movement", "Cognitive Ability", "Sociality" and "Living Habits" (5.65±0.59, p<0.01; 11.20±1.91, p<0.05; 9.05±1.72, p<0.05; 7.10±1.45, p<0.05) in mental health outcomes. Diverse exercise has a significantly beneficial role in promoting the cognitive development of children aged 5-6 years, as well as a beneficial, albeit insignificant, role in their mental health.